Evaluation of stone mastic asphalt (SMA) mixtures as related to permeability [compact disc] - 207796 Hong, Tian Peng (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2005